1987
DOI: 10.1099/0022-1317-68-9-2359
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Membrane Components of the Erythrocyte Involved in Vesicular Stomatitis Virus Attachment and Fusion at Acidic pH

Abstract: SUMMARYGoose erythrocyte membranes were isolated and tested for their ability to compete with red cell receptors for vesicular stomatitis virus (VSV) attachment and fusion at acidic pH. Crude membranes, solubilized with Triton X-100, Tween 80 and octyl-/~-Dglucopyranoside, showed a dose-dependent inhibitory effect on virus binding and haemolysis. The chemical nature of the active molecules was investigated by enzyme digestion and by separation of purified components. Only the lipid moiety, specifically phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 19 publications
1
75
0
4
Order By: Relevance
“…The results obtained by Mastromarino et al (31) using erythrocytes at acidic pH showed that, besides PS, phosphatidylinositol and GM3 ganglioside also inhibited VSV attachment to cells. Removal of the charged groups from these negatively charged molecules greatly reduced their inhibitory activities, suggesting an important role of electrostatic interactions during cell recognition by VSV.…”
Section: Rhabdovirus Binding To the Cell Surfacementioning
confidence: 81%
See 1 more Smart Citation
“…The results obtained by Mastromarino et al (31) using erythrocytes at acidic pH showed that, besides PS, phosphatidylinositol and GM3 ganglioside also inhibited VSV attachment to cells. Removal of the charged groups from these negatively charged molecules greatly reduced their inhibitory activities, suggesting an important role of electrostatic interactions during cell recognition by VSV.…”
Section: Rhabdovirus Binding To the Cell Surfacementioning
confidence: 81%
“…Phospholipids from cellular membranes inhibit attachment and infection of rabies virus and VSV (30)(31)(32). Indeed, the VSV host range extends from nearly all mammals to insects, suggesting that the receptor for this virus is a widely distributed molecule.…”
Section: Rhabdovirus Binding To the Cell Surfacementioning
confidence: 99%
“…As linkage to CS-BoTIM/B did not abolish the viral tropism for muscle cells, the gain in neurotropism could reflect the cooperative binding of targeted lentivirus to the BoNT/B neuronal ecto-acceptor along with vesicular stomatitis virus glycoprotein interaction with phospholipids in the cell membrane. 35 Such a simple mechanism could also explain the enhanced transduction of the CS-BoTIM/B-targeted GFP vector to intramural ganglionic neurons in vivo. Unlike the non-targeted lentivirus, which is more likely to dissipate through systemic clearance from the interstitial tissue of the tracheal wall after injection and yield indiscriminate GFP expression at the SI, the CS-BoTIM/B-linked lentivirus would tend to remain longer in the tissue because of its high-affinity binding to neurons, thereby amplifying production therein of the reporter.…”
Section: Activity Dependence and Selectivity Of Cs-botim/b Entry Intomentioning
confidence: 99%
“…As the VSV-G envelope is thought to bind to cell surface phospholipids, 27,28 VSV-G -pseudotyped lentivirus vectors have a potential advantage over adenovirus serotype 5 -based vectors in their ability to achieve efficient gene delivery to cancer cells even if they lack specific cell surface proteins that normally act as receptors for virus entry. Furthermore, another advantage of lentivirus vectors is their potential to achieve stable integration and long -term expression of delivered transgenes.…”
Section: Autocrine Inhibition Of Endothelial Cell Growth By Direct Trmentioning
confidence: 99%